Foxd1 is a mediator and indicator of the cell reprogramming process - Koga, Makito; Matsuda, Mitsuhiro; Kawamura, Teruhisa; Sogo, Takahiro; Shigeno, Asako; Nishida, Eisuke; Ebisuya, Miki (Nature communications, 2014)
It remains unclear how changes in gene expression profiles that establish a pluripotent state are induced during cell reprogramming. Here we identify two forkhead box transcription factors, Foxd1 and Foxo1, as mediators of gene expression programme changes during reprogramming. Knockdown of Foxd1 or Foxo1 reduces the number of iPSCs, and the double knockdown further reduces it. Knockout of Foxd1 inhibits downstream transcriptional events, including the expression of Dax1, a component of the autoregulatory network for maintaining pluripotency. Interestingly, the expression level of Foxd1 is transiently increased in a small population of cells in the middle stage of reprogramming. The transient Foxd1 upregulation in this stage is correlated with a future cell fate as iPSCs. Fate mapping analyses further reveal that >95% of iPSC colonies are derived from the Foxd1-positive cells. Thus, Foxd1 is a mediator and indicator of successful progression of reprogramming. The forkhead box transcription factor Foxo1 is required for the maintenance of pluripotency in human embryonic stem cells. Here Koga et al. show that expression of another forkhead box transcription factor, Foxd1, promotes and indicates successful reprogramming of mouse embryonic fibroblasts.